2010
DOI: 10.1111/j.1540-8159.2009.02551.x
|View full text |Cite
|
Sign up to set email alerts
|

Sick Sinus Syndrome in a Patient with Extensive Cardiac Lipomatosis (Sinus Node Dysfunction in Lipomatosis)

Abstract: We present a case of a 45-year-old man with an incidental and longstanding diagnosis of extensive mediastinal and cardiac lipomatosis. Along the years, he had experienced various arrhythmias, mainly bradyarrhythmias, mostly asymptomatic. Recently after documenting a sinus pause of 6 seconds and runs of nonsustained ventricular tachycardias, he underwent an implantation of a cardioverter-defibrillator. There are many reports of cardiac lipomatosis in the literature, including reports of related ventricular arrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Additionally, a previous study showed that a few cases of SND had extensive cardiac lipomatosis as a disease-causing lesion. 7 Our Case 1 showed that reduction in functional nodal cells may be a more common pathological substrate of advanced SND rather than fibrosis and/or fatty infiltration in many cases.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Additionally, a previous study showed that a few cases of SND had extensive cardiac lipomatosis as a disease-causing lesion. 7 Our Case 1 showed that reduction in functional nodal cells may be a more common pathological substrate of advanced SND rather than fibrosis and/or fatty infiltration in many cases.…”
Section: Discussionmentioning
confidence: 74%
“…fatty infiltration or neoplastic change, have been reported as pathological substrates for bradyarrhythmia, and advanced fibrosis was not observed in such cases. 7 Therefore, objective morphological investigation into the amount of conduction fibers may be important for considering the etiology of idiopathic bradyarrhythmia. Moreover, the etiology of degeneration and/or fibrosis in the conduction system in idiopathic bradyarrhythmia cases has not yet been explored.…”
mentioning
confidence: 99%
“…In the reported case, the absence of significant fibrosis and/or degenerative myocytic changes were in favour of fatty infiltration of both right atrium and ventricle. Various arrhythmias and conduction disturbances have been reported in association with this condition [1]. In the most frequent type of cardiac lipomatosis, the infiltration of the interatrial septum, commonly cause premature atrial contractions, supraventricular tachycardia and atrial fibrillation [4], conversely, the involvement of the atrio-ventricular node can lead to a conduction block [5].…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, since the patients are typically asymptomatic, this finding is incidental, found either by imaging studies or during autopsies [1]. Over 200 cases have been described [1] in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation